Nexus between Stock Market Prices and Some Macroeconomic Indicators in Nigeria - I. P. Abu; S. C. Nwaosu; J. A. Ikughur (Journal of Applied Sciences and Environmental Management)
The problem of identifying the relationship among macroeconomic variables have been a challenge in developing countries due to frequent changes in policy that alter their behaviors contrary to expectations. Thus, this study is aimed at empirically examining the link between stock market prices and some macroeconomic indicators in Nigeria covering the period January, 2004 to June, 2024. Results revealed that the variables were all integrated of order one, I(1) and a long-run stable equilibrium relationship existed among the variables. Exchange rate and money supply had significant positive impact on stock market prices while inflation rate and interest rate had significant negative impact on stock market prices in Nigeria. The error correction model showed a high speed of adjustment of 99.998% to achieving long-run equilibrium steady state in the Nigerian economic system. Results of the VAR Granger causality test revealed that exchange rate and money supply both have a one-way causative effect on stock prices and inflation rate. Furthermore, inflation rate Granger causes stock market prices, but stock prices do not influence inflation. Moreover, there is bidirectional causality between exchange rate and money supply, indicating that changes in each variable mutually affect the other. The study recommends the evolution of policies to stabilize the exchange rate and money supply, manage inflation and interest rates carefully, monitor the bidirectional relationship between exchange rate and money supply, and engage in long-term economic planning.